Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1513/pats.200603-060ms
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Airway Inflammation by Haemophilus influenzae Isolates Associated with Chronic Obstructive Pulmonary Disease Exacerbation

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) has been associated with lower airway, systemic, and, more recently, upper airway inflammation. The systemic component may be important through an association with increased cardiovascular comorbidity. While it is known that lower airway and systemic inflammation are increased at exacerbation of COPD (Ex)-COPD, it is not known whether the upper airway is involved at this time, nor how the upper airway, lower airway, and systemic compartments relate dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…NTHi is commonly isolated from the nasopharynx of healthy individuals, but is also associated with chronic airway diseases such as bronchiectasis [37] , COPD [38] , and chronic bronchitis [39] . NTHi is the bacterium most commonly isolated during COPD exacerbations, and NTHi strains isolated during these exacerbations induce higher levels of IL-8, and subsequent neutrophil recruitment to the airways, than colonizing strains [40] . Simpson and colleagues have recently demonstrated that a large proportion of neutrophilic asthmatics are colonized with H. influenzae , have increased innate immune activation, and 6-8 fold higher endotoxin levels compared to other asthma subtypes and healthy controls [12] .…”
Section: Discussionmentioning
confidence: 99%
“…NTHi is commonly isolated from the nasopharynx of healthy individuals, but is also associated with chronic airway diseases such as bronchiectasis [37] , COPD [38] , and chronic bronchitis [39] . NTHi is the bacterium most commonly isolated during COPD exacerbations, and NTHi strains isolated during these exacerbations induce higher levels of IL-8, and subsequent neutrophil recruitment to the airways, than colonizing strains [40] . Simpson and colleagues have recently demonstrated that a large proportion of neutrophilic asthmatics are colonized with H. influenzae , have increased innate immune activation, and 6-8 fold higher endotoxin levels compared to other asthma subtypes and healthy controls [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic bacterial colonization of the airways contribute to the inflammatory response of COPD [ 13 ] and to disease progression [ 14 16 ]. Airway infection is also a key pathogenic mechanism of COPD exacerbations [ 13 , 15 , 17 19 ] which, are characterized by a flare-up of airway inflammation [ 20 22 ]. Non-typeable Haemophilus influenzae (NTHi) is frequently isolated from COPD patients both when clinically stable and during exacerbations [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the typeable strains, H. influenzae type b (Hib) is considered to be most virulent causing bacteraemia, pneumonia and acute bacterial meningitis or occasionally, osteomyelitis, epiglottitis and joint infections (Watt et al ., 2009). Non‐typeable H. influenzae (NTHi) is most commonly associated with otitis media, sinusitis and chronic obstructive pulmonary disease (COPD) (Murphy, 2003; Sethi et al ., 2004, Look et al ., 2006). A crucial factor in the H. influenzae pathogenesis involves the initial adherence to the respiratory mucosa.…”
Section: Introductionmentioning
confidence: 99%